Performance, emission and combustion characteristics of Sea lemon oil and its diesel blends in a diesel engine - Hariharan, V. S.; Reddy, K. Vijayakumar; Rajagopal, K. (International Journal of Agricultural and Biological Engineering, 2009)
Experimental tests have been carried out to evaluate the performance, emission and combustion characteristics of a diesel engine using neat sea lemon oil and its blends of 25%, 50%, & 75% and standard diesel fuel separately. The common problems posed when using vegetable oil in a compression ignition engine are poor atomization, carbon deposits, ring sticking etc. This is because of the high viscosity and low volatility of vegetable oil. When blended with diesel, sea lemon oil presented lower viscosity, improved volatility, better combustion and less carbon deposit. It was found that there was reduction in NO for neat sea lemon oil and its diesel blends along with marginal increase in smoke, HC and CO emissions compared to that of standard diesel. Brake thermal efficiency was slightly lower for neat sea lemon oil and its diesel blends. From the combustion analysis, it was found that sea lemon oil-diesel blends performed better than neat sea lemon oil. Keywords: sea lemon oil, blends, performance, emission and combustion characteristics DOI: 10.3965/j.issn.1934-6344.2009.03.069-075 Citation: V. S. Hariharan, K. Vijayakumar Reddy, K. Rajagopal. Performance, emission and combustion characteristics of sea lemon oil and its diesel blends in a diesel engine. Int. J Agric & Biol Eng, 2009; 2(3): 69